The Microbial Fuel Cell Characteristics of the PVA/Chitosan Membrane with Variations of Phosphate Acid and Sodium Alginate Derived from Vegetable Waste - Nugraha, Iqbal Adi; Supriyanto, Amir; Pauzi, Gurum Ahmad; Junaidi, Junaidi (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
Microbial Fuel Cell (MFC) is one of the alternative energy sources as a producer of vegetable waste. The membrane that is commonly used in the MFC system is the Nafion membrane, but it is expensive and must be imported. PVA membrane and chitosan are an alternative substitute for Nafion membrane. The purpose of this study was to determine the electrical performance of variations of PVA/Chitosan membrane with the addition of sodium alginate or phosphoric acid. The study used a dual chamber MFC system made of acrylic with a volume of ±250 ml for each compartment. The anode compartment contains vegetable waste with carbon electrodes, and the cathode compartment contains seawater electrolytes with Cu(Ag) electrodes. The MFC system consists of 10 cells in series. From the study results, it was concluded that the vegetable waste substrate with the addition of EM4 bacteria could be used as an alternative energy source. The use of variations on the PVA/Chitosan membrane without addition produces the highest maximum voltage level of 2.25 volts compared to the addition of sodium alginate or phosphoric acid of 2.25 volts, 1.941 volts, and 2.1 volts.